Characteristics and share of European beech false heartwood in felling sites of Central Croatia - Prka, Marinko (Array, 2009)
Summary: False heartwood, as the phenomenon considerably affecting the quality of beech logs and trees, has been the object of professional and scientific interest for more than 100 years. Occurrence and characteristics of false heartwood were investigated depending on diameter class of average trees and type of cut in beech stands on a sample of 2308 trees. The age of trees in thinnings ranges between 50 and 91, in preparatory cuts between 96 and 111, in seeding cuts between 101 and 112 and in final cuts between 98 and 112. In thinnings 11.7% of trees were found with false heartwood, in preparatory cut 54.7%, in seeding cut 71.3% and in final cut 84.6%. The length of processed logs, and absolute shares of false heartwood in trees, increase from thinning to final cut, while the volume percentage of false heartwood in trees for all types of cuts, except final cut, decreases.With seeding and final cuts approximately 15% of volume of processed assortments of the highest quality (A and B quality class) has an excessive share of sound false heartwood for Aand B quality class.With respect to the volume of large wood, depending on diameter class, the share of quality subclass A–s ranges between 0.3 and 2% and the share of quality subclass B-s between 1.1 and 3.2% of large wood volume